ANALISIS BUTIR SOAL TES AKHIR SEMESTER (TAS) KIMIA SMA NEGERI II AMBON TAHUN PELAJARAN 2014/2015 - Fatma Al Hamid; Yance Manoppo; Victor Kayadoe (Program Studi Pendidikan Kimia FKIP Universitas Pattimura, 2018)
The aims of this research was to analyze the exam questions in the end of semester tests SMA Negeri II Ambon year of 2014/2015. The item tests was analized include the validity, reliability, power of difficulty, discrimination power, and distractor effective. This research type was kuantitative descriptive method and the data was analyzed by using Item and Test Analysis (Iteman) Program. Subjects of this research are test instrument and student answer results of chemical tests at odd semester class X SMA Negeri II Ambon year. Documentation technik was used to collect data. Results of the analysis showed that the quality which was seen from the validity, there were 80% of questions which were valid and the rest there were 20% were invalid. Reliability indeks is 0,733. From the level of difficulty, there were 8 easy questions, 22 medium questions, and 20 hard question. From the discrimination power, there were 42 questions or 84% questions which had good discrimination power and there were 8 or 16% questions which had low and negative. Meanwhile from the answer patterns, it is known that 60% destructor in the questions were function properly and 40% were function unproperly